A review of task allocation methods for UAVs - Skaltsis, George Marios; Shin, Hyo-Sang; Tsourdos, Antonios (Springer, 2023)
Unmanned aerial vehicles, can offer solutions to a lot of problems, making it crucial to research more and improve the task allocation methods used. In this survey, the main approaches used for task allocation in applications involving UAVs are presented as well as the most common applications of UAVs that require the application of task allocation methods. They are followed by the categories of the task allocation algorithms used, with the main focus being on more recent works. Our analysis of these methods focuses primarily on their complexity, optimality, and scalability. Additionally, the communication schemes commonly utilized are presented, as well as the impact of uncertainty on task allocation of UAVs. Finally, these methods are compared based on the aforementioned criteria, suggesting the most promising approaches.
Keywords: Task allocation; UAVs; Auction based algorithms; Optimisation; Reinforcement learning; Game theory; Metaheuristics